An extremely high bioavailability of orally administered vancomycin in a patient with severe colitis and renal insufficiency. Issue 12 (December 2017) - Yamazaki, Shingo; Suzuki, Takaaki; Suzuki, Tatsuya; Takatsuka, Hirokazu; Ishikawa, Masayuki; Hattori, Noriyuki; Fujishiro, Takeshi; Miyauchi, Hideaki; Oami, Takehiko; Ariyoshi, Noritaka; Oda, Shigeto; Matsubara, Hisahiro; et al.
Abstract: Because there is little absorption of orally administered vancomycin hydrochloride (VCM) through the normal intestinal microvillus membrane, the pharmacokinetics of VCM absorbed from the digestive tract are mostly unknown. Here we report a case of severe colitis and renal insufficiency in which the serum concentration of VCM reached the supratherapeutic range after oral administration. A 54-year-old man receiving outpatient chemotherapy for rectal cancer was admitted to our hospital for severe sepsis and acute renal failure. Multimodal therapy including continuous renal replacement therapy (CRRT) and mechanical ventilation was initiated, and oral VCM administration (0.5 g every 6 h) was begun for suspected severe pseudomembranous colitis with large amounts of watery stool. Despite continued CRRT, the serum VCM concentration increased to 30.6 μg/mL after 4 days. Based on pharmacokinetic analysis, the bioavailability of VCM was estimated to be over 54.5%. Colonoscopy showed that the mucosa was severely damaged throughout the large intestine, resulting in considerable exudation of plasma and blood. This case indicates the need for careful and early monitoring during high-dose oral VCM administration to patients with severe mucosal injury and renal insufficiency.